EFEKTIVITAS PENERAPAN PERATURAN FULL DAY SCHOOL BAGI PESERTA DIDIK TINGKAT MI DI MI PLUS JÁ-ALHAQ - Hidayaturrahman, M.; Fadlillah, Andini; Diah Parmitha, Rike; Kusmiati, Kusmiati; Wafiq Azizah, Anisa (Jurnal Ilmu Pendidikan Islam, 2025)
This research aims to analyze the effectiveness of implementing Full Day School regulations for Madrasah Ibtidaiyah (MI) level students at MI PLUS JA-ALHAQ Bengkulu City. discipline and student learning achievement, but also raises challenges such as physical and mental fatigue. In conclusion, the implementation of Full Day School is effective in improving the method used in this research is a qualitative descriptive method with data collection techniques through observation, interviews and documentation. The research results show that the implementation of Full Day School has a positive impact on improving the quality of education if it is balanced with fun learning strategies and support from various parties, including teachers, parents and the school environment..